ANALYSIS OF THE POTENTIAL AND OBSTACLES TO ESTABLISHING A VILLAGE-OWNED ENTERPRISE (BUMDES) IN THE GUNTUR SUBDISTRICT, DEMAK REGENCY - Nugroho Tulus Rahayu; Ariyani Indriastuti (Sekolah Tinggi Ilmu Ekonomi Semarang, 2020)
Village-Owned Enterprises or BUMDes are pillars of economic activity in the village, which strengthens the village economy. BUMDes is formed by the village government based on the needs and potential of the village. In the Guntur subdistrict, Demak regency, 2 BUMDes have been established, namely SidorukunBUMDes in Sidokumpul village and SumberlancarBUMDes in Bakalrejo village. Eighteen other villages do not yet have BUMDes. The purpose of this study was to determine the initiative of the village government in establishing BUMDes, find out what the potential of the village to establish BUMDes, determine the obstacles in establishing BUMDes. The population of this research is the village government in the Guntur subdistrict, which consists of 20 villages and BUMDesSidorukun and BUMDesSumberLancar. The method used is the census method. Data obtained by interview. The analytical method used is descriptive analysis. The results of this study found that the initiative of the village government in the Guntur sub-district of Demak district in establishing BUMDes was still low. Potentials that can be managed by BUMDes include potentials in agriculture, rice, corn and green beans, cow and goat farms, village markets, and pure water. The obstacles in establishing BUMDes stem from the village government's understanding of BUMDes that is still low.